Calculation of Flight Data Fusion Coefficients Using Newton–Raphson Iterations - Sabziev, Elkhan Nariman (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
The problem of plotting the flight path of an aircraft based on flight data containing numerous measurement errors is investigated. A theoretical (continuous) model of the flight data fusion problem is proposed in the form of a boundary value problem for a system of differential equations with unknown coefficients. The application of the Newton–Raphson iteration method for calculating the sought-for coefficients is described.